TECHNOLOGIES FOR ELIMINATING SPEECH DEFECTS IN CHILDREN WITH PROBLEMS IN THE MUSCULOSKELETAL SYSTEM IN PRESCHOOL AGE - Makhmudova Madinakhon Sobirkhonovna; Isodullayeva Iqboloy Sadigjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article covers the types of children's cerebral palsy, causes of origin and issues of organizing special care